PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO ONLINE LAKUSTORE.NH DI SITUBONDO - Nurafifa, Indah Ayu; Tulhusnah, Lusiana; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Marketing has a role to recognize the needs and desires of consumers, and ensure consumers get good service from the company. The purpose of this study was to analyze and test the effect of service quality and price on consumer loyalty through consumer satisfaction. The population in this study were consumers of the Lakustore.NH Online Store in Situbondo. The sampling technique in this study used a simple random sampling technique. Data analysis and hypothesis testing in this study used the Partial Least Square - Structural Equation Model (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application showed that Service quality had a significant positive effect on Customer satisfaction, Price had a significant positive effect on customer satisfaction, Service quality had a significant positive effect on customer loyalty, Price had a significant positive effect on Customer loyalty, Consumer satisfaction had a significant positive effect on Customer loyalty. The results of the indirect effect hypothesis test showed that the Service quality variable on Consumer loyalty through Customer satisfaction had a significant positive effect, Price on consumer loyalty through Customer satisfaction had a significant positive effect.